2008
DOI: 10.1111/j.1469-8137.2008.02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth on nitrate and occurrence of nitrate reductase‐encoding genes in a phylogenetically diverse range of ectomycorrhizal fungi

Abstract: Summary• Ectomycorrhizal (ECM) fungi are often considered to be most prevalent under conditions where organic sources of N predominate. However, ECM fungi are increasingly exposed to nitrate from anthropogenic sources. Currently, the ability of ECM fungi to metabolize this nitrate is poorly understood.• Here, growth was examined among 106 isolates, representing 68 species, of ECM fungi on nitrate as the sole N source. In addition, the occurrence of genes coding for the nitrate reductase enzyme (nar gene) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 67 publications
(81 reference statements)
3
72
0
Order By: Relevance
“…Genomic DNA from C. rosea WT was extracted using a hexadecyl-trimethyl-ammonium bromide-based protocol (Nygren et al, 2008). Approximately 1200 bp of 59 and 39 flanking regions of the chiC2 gene were amplified from genomic DNA by PCR using the primer sequences listed in Table S2, while the hygromycin-resistance gene (hygB) was amplified from the pCT74 vector (Lorang et al, 2001) as described previously (Dubey et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA from C. rosea WT was extracted using a hexadecyl-trimethyl-ammonium bromide-based protocol (Nygren et al, 2008). Approximately 1200 bp of 59 and 39 flanking regions of the chiC2 gene were amplified from genomic DNA by PCR using the primer sequences listed in Table S2, while the hygromycin-resistance gene (hygB) was amplified from the pCT74 vector (Lorang et al, 2001) as described previously (Dubey et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…This approach has also been used to screen for other enzymeencoding genes in a phylogenetically wider range of ectomycorrhizal fungi (Lindahl and Taylor, 2004;Nygren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1) and in the field (Clemmensen et al 2008). In pure culture, Nygren et al (2008) demonstrated wide variation among 68 species of ECM fungi in their mycelial growth with nitrate as the sole N source. While results of culture studies must be used with caution because they may not reflect N preferences of ECM fungi when growing in symbiosis with trees (Turnbull et al 1995), Hobbie et al (2008) also demonstrated higher nitrate uptake and greater inferred transfer of N from fungus to plant by Laccaria laccata (Scop.)…”
Section: Ecm Fungal Species Differ In N Form Preference and Uptakementioning
confidence: 98%